Fabrication of High Aspect‐Ratio Surface Micro Patterns on Stainless Steel using High‐Speed Direct Laser Interference Patterning. Issue 7 (16th April 2019) - Lang, Valentin; Voisiat, Bogdan; Kunze, Tim; Lasagni, Andrés Fabián
Abstract : This work addresses the fabrication of periodic micro patterns on stainless steel by means of Direct Laser Interference Patterning. A modular optics assembly is introduced which produces two‐beam interference patterns within a 5 × 100 μm rectangular shaped laser spot. The optical assembly considers optimal utilization of the available laser power in order to enable high processing rates. Using different optical elements, the spatial period of the periodic structures was set to 8 μm and 19 μm. The effect of the processing parameters on the morphology of the produced patterns is investigated by means of confocal microscopy, scanning electron microscopy, and energy‐dispersive X‐ray spectroscopy. It is found that the pulse repetition rate shows a strong influence on the structure height accompanied by considerable heat accumulation effects, which is reported for the first time for this method. In addition, aspect ratios slightly higher than one could be realized, which is also reported for the first time when using Direct Laser Interference Patterning with ns‐pulsed lasers. Particularly for the smaller periods, the melt flow impairs pattern formation due to the overmelting of the material (humping). Moreover, variations of the surface chemistry are observed, especially for higher accumulated laser fluences. Abstract : A modular optics assembly is introduced for the treatment of steel surfaces enabling high processing rates for two‐beam interference (period of 8 μm and 19 μm) within a 5 × 100 μm shaped laser spot. The pulse repetition rate shows a strong influence on the structure height due to heat accumulation effects.